A new troglobitic species of the genus Pholeuonopsis (Coleoptera: Leiodidae: Cholevinae: Leptodirini) from western Serbia, with a key to the species from Serbia - Ćurčić, Srećko; Vrbica, Maja; Vesović, Nikola; Antić, Dragan; Petković, Matija; Bosco, Fabrizio; Ćurčić, Božidar (Zootaxa, 2015)
A new leptodirine leiodid beetle species, Pholeuonopsis (Pholeuonopsis) sljivovicensis sp. n., from a cave in western Serbia is described and diagnosed. The views of both male and female genitalia and other taxonomically important characters are imaged. The new species is clearly distinct from the closest relatives. It probably belongs to an old phyletic lineage of Mesogeid origin, like other known Pholeuonopsis taxa from the western part of the Balkan Peninsula. The new species is both an endemic and a relict inhabiting solely western Serbia. Morphological comparisons among the Serbian Pholeuonopsis species are provided, together with a key to the species. The genus Serbopholeuonopsis B. Ćurčić & Boškova, 2002 is regarded as a junior synonym of the genus Pholeuonopsis Apfelbeck, 1901.